Analisis Pelaksanaan Pelayanan Informasi Corona Virus Disease 19 Di Kabupaten Ogan Komering Ulu - Asteriniah, Femi; Ardianita, Erfina; Idris, Umiyati (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
The purpose of analyzing the implementation of information services for coronavirus disease 19 in Ogan Komering Ulu Regency. This study uses a qualitative descriptive analysis technique. The conclusions of this study are as follows (1). Planning for information services for the corona virus 19 in OKU Regency is going well, the purpose of this policy is to find out information about this covid19, in the context of preventing and reducing the impact of transmission, according to the Information Commission Circular (SE) Regulation No: 02 of 2020 concerning Guidelines for Public Information Services in Public Health Emergency Due to Corona Virus Disease 2019 (Covid19). (2). There are 13 organizations with indicators of staffing implementation, organizational structure and division of labor for human resources in the 19 corona disease information service in OKU Regency. (3). The amount of Deployment for reporting COVID-19 cases in OKU Regency, which can be done on the official portal, at Diskominfo and on the official OKU Regency government portal, but the existing mechanism is compiled from the health office through the Ogan Puskesmas Komering Ulu Regency. The implementation provides information on immunization achievements in OKU District, in general there is already a COVID 19 task force in OKU District, but the OKU District information and communication service always provides information regarding vaccination achievements through the official website and social media owned by Diskominfo. in the form of information provided by the public, such as information services that can be accessed through the official website of Diskominfo OKU. (Ogan Komering Ulu). The monitoring measure for the monitoring stage is the existence of internal and external monitoring at the OKU District Communication and Information Office.